LGG-62. Weight change in pediatric patients treated with MEK inhibitors: a retrospective cohort study. (3rd June 2022) - Hyun Bahng, Hye; Malvar, Jemily; Chi, Yueh-Yun; Framson, Celia; Robison, Nathan
Abstract: BACKGROUND: MEK inhibition is an emerging treatment strategy in pediatric tumors characterized by activation of the Ras-Raf-MEK-ERK pathway, including low-grade glioma (LGG) and neurofibromatosis 1 (NF1)-associated tumors. Preliminary clinical experience suggests that MEK inhibitors (MEKi) may be associated with weight gain in children, which has not been a reported toxicity in adults. METHODS: 35 patients > 1 and < 21 years old treated at CHLA with MEKi between October 2013 and May 2019 were identified. Data was collected at t = 0 (baseline), t = 3 months, t = 6 months, t = 12 months, and t = 24 months, as well as pre- and post-treatment time points. Weight change was categorized as no change (change in Z-score [-0.25, +0.25]), weight gain (change in Z-score > 0.25), and weight loss (change in Z-score > -0.25). RESULTS: Weight gain and weight loss were seen in 11 (34.4%) and 8 (25%) patients, respectively, after 6 months on therapy. Weight gain reversed in 4 out of 5 patients with post-treatment data. There was no clear association between weight outcome and hypothesized covariates (including hypothalamic location and NF1 status). Notably, significant weight gain was seen across baseline weight spectrum, including patients who had underweight and severely overweight BMI percentiles at baseline. CONCLUSION: Our findings preliminarily suggest that MEK inhibition may be associated with clinically significant weight change, especially weight gain, in a subset of children and young adults. Reversal upon drug cessation suggests a causal relationship. Further prospective and mechanistic investigation is needed.